2020
DOI: 10.2196/21922
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges and Opportunities Associated With the Ability to Perform Medical Screening From Interactions With Search Engines: Viewpoint

Abstract: Recent research has shown the efficacy of screening for serious medical conditions from data collected while people interact with online services. In particular, queries to search engines and the interactions with them were shown to be advantageous for screening a range of conditions including diabetes, several forms of cancer, eating disorders, and depression. These screening abilities offer unique advantages in that they can serve a broad strata of the society, including people in underserved populations an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…This study further demonstrates the potential of search engine investigations using data from unidentified users to provide information about the health of populations under-represented in traditional medical research 20 . Our data suggest that using search engine data, we can recognize a group of users who are likely to have ALS and detect unique search characteristics that distinguish this group from controls with a high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This study further demonstrates the potential of search engine investigations using data from unidentified users to provide information about the health of populations under-represented in traditional medical research 20 . Our data suggest that using search engine data, we can recognize a group of users who are likely to have ALS and detect unique search characteristics that distinguish this group from controls with a high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 65%
“…Past work on screening from internet data used predominantly archival data, where the endpoints used to identify the patient cohort were queries in which users self-identified as having the condition of interest. This offers a method for creating patient cohorts with relatively little recruiting effort, but the patient cohort is not clinically validated, and relying exclusively on this analysis could raise ethical challenges 20 . An alternative, face-to-face recruitment of patients, is challenging in the case of rare diseases such as ALS.…”
Section: Introductionmentioning
confidence: 99%
“…This study has further demonstrated the potential of search engine investigations using data from unidentified users to provide information about the health of populations underrepresented in traditional medical research. 17 F I G U R E 4 Receiver-operating characteristics curve (prospective, self-identified participants). The AUC distinguishes people with selfidentified amyotrophic lateral sclerosis (ALS) from controls.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional data are often collected under the full control of the investigator, following a carefully monitored intervention. Internet data are collected for the two following main reasons, neither of which is research: to provide information to users and to facilitate improving the service that provides them [ 13 ]. Thus, researchers have no control over the type of data and when they are collected.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, people often only implicitly consent to the terms of use through the use of the service, that is, there is a statement indicating that the use of the service implies consent to the terms of use. Although the full terms of service are provided as a link on the service’s page, only a tiny minority of users (fewer than 0.1% in one case) click on this link [ 13 ]. Other mechanisms of consent (eg, a pop-up window) have not fared significantly better [ 15 ].…”
Section: Introductionmentioning
confidence: 99%